Uso de bagaço de caju como suporte para a imobilização de lipase do tipo B de Candida antarctica: aplicação na síntese de R-indanol - Souza, Ticiane Cavalcante de (2016)
The cashew apple bagasse (CAB), an agroindustrial wastes, was used as a support for the immobilizing of lipase kind B de Candida antarctica (CALB). After treatment with alkaline hydrogen peroxide (AHP), CAB - AHP was f unctionalized with glycidol (GLY ), epichlorohydrin (EPI), glycidol – ethylenediamine - glutaraldehyde (GEG) 5% and 10% and then, characterized through analysis of the Scanning Electron microscopy ( MEV ) and Red Infra Fourier Transform (FTIR). The biocatalysts produced at pH 10 (25 mM, 25 °C, 0.5% Triton® X - 100) and at pH 7 (5 mM, 100 mM, 25 °C, 0.5% Triton® X - 100), were characterized with respect to thermal stability, stability in the presence of organic solvents, pH relationship and hydrolytic activity. The derivatives were applied in the enzymatic kinetic resolution of rac - acetate indanila (30 °C, 24h, 250 rpm). The biocatalyst produced at pH 10.0, CAB - GLI and CAB - EPI showed high swelling and low catalytic activity (0.22 ± 0.19 U/g and 0.21 ± 0.22 U/g) respectively. The CAB - GEG 5%, in the presence and in the absence of 0.5% Triton® X - 100, showed high catalytic activities (21.8 ± 0.52 U/g 38.8 ± 0.37 U/g) and high immobilization yields (95.1% and 97.1%), respectively. The longest times of half - life t 1/2 were obtained under as say conditions at 60 °C and pH 5.0, 32.9 minutes for the immobilized prepared in the absence of Triton® X - 100 and 29.8 minutes with addition of detergent. The stability in the presence of tetrahydrofuran solvent (THF) was best achieved when the derivative was prepared with addition of 0 .5% Triton® X - 100, showing t 1/2 of 60 minutes. For the derivatives produced at pH 7.0, CAB - GEG 10% (5 mM) in the presence of detergent showed enzymatic activity of 29.62 ± 0 74 U / g. This derivative showed the best immobilization parameters in assays at pH 7.0. The most sta ble derivative at 60 °C showed t 1/2 of 100.7 minutes (CAB - GEG 10%, 5 mM at pH 5.0). For the stabilities to organic solvents in the presence of tetrahydrofuran, the biocatalyst obtained in higher i onic strength conditions (100 mM) and in the presence of detergent was the most stable, t 1/2 129.7 minutes. The derivatives were applied in the enzymatic kinetic resolution of rac - acetate indanol, showing high conversion values (50%). They can be applied i n the production of intermediates used in drug formulations, such as Rasagiline Mesylate, indicated for the management of Parkinson's disease